RESEARCH ABOUT THE AGE OF GEOMORPHOLOGICAL PROCESSES USING THE ARCHAEOLOGICAL DATA IN ALBA IULIA AREA (PANGEEA, 2025)
Research about the age of geomorphological processes using the archaeological data in Alba Iulia area. This paper contribute to establishing the age of floodplain terraces through the use of archaeological methods to study morphogenetic terraces. The method was applied to the terraces of the river Mures, in Alba Iulia depression area.